Influencing factors riding safety behavior in students of Vocational High School Negeri 3 Sorong City: Influencing factors riding safety behavior in students of Vocational High School Negeri 3 Sorong City - Jenni Lilis S Siagian; Astuti R; Hansen Maikel Su (Institute of Computer Science (IOCS), 2023)
Limited public transportation causes parents to use motorized vehicle ownership as an alternative, so that many children under 17 years old and even 10 years old are already using motorized vehicles. This lack of maturity will have a negative impact on child safety. Based on the interview results, it was found that students did not have a driver's license, did not use personal protective equipment, drove at high speed and had had an accident. The purpose of this study was to determine the effect of knowledge, attitudes, driving license ownership and driving experience on safety riding behavior at SMK Negeri 3 Sorong City. This type of research is quantitative with a cross sectional approach. The research population is all students who are currently at school (not currently practicing), namely a sample of 87 people. The instrument used was a questionnaire, and data analysis used the Spearman Rank test with α = 0.05. the test results show that knowledge, p-value = 0.04, attitude = 0.011, driving license = 0.020 and driving experience = 0.181. It was concluded that there was an effect of knowledge, attitude and ownership of a driver's license while driving experience had no effect on safety riding behavior.